A Comparison between FARSITE and FOREFIRE - Paugam, Ronan; Sánchez, Paula; González, Irene; Carrillo, Carlos; Filippi, Jean Baptiste (Journal of physics. Conference series, 2025)
Accurate fire spread modeling is essential for understanding and mitigating the impacts of wildfires. This study compares two fire spread models, FARSITE and FOREFIRE, by reconstructing the 2022 wildfire in El Pont de Vilomara, Spain. Both models use the Rothermel rate of spread (ROS) equation to model fire behavior, however, FOREFIRE employs a simplified fuel classification system, which may impact the accuracy of its predictions. Our analysis evaluates fire spread predictions in 0D (ROS), 2D (fire perimeter), and 3D (plume dynamics) simulations. Results show that FARSITE underestimates fire propagation, while FOREFIRE overestimates it, both requiring ROS adjustments to match observation. The coupled FOREFIRE-MesoNH require also ROS adjustment but better incorporates fire behavior representation.